Mitochondrial DNA evolution and its utility for population genetic studies of Phytophthora infestans - Gavino, Pia Demetillo (UMI Company, 1999)
The evolution of the mitochondrial genome of Phytophthora infestans (Mont.) de Bary was investigated and this new information was applied to gain a more clear understanding of the population genetics of the oomycete pathogen causing late blight disease on potatoes and tomatoes. The two systems of mitochondrial DNA (mtDNA) nomenclature were reconciled by comparing isolates that represent six mtDNA haplotypes of P. infestans. A mtDNA phylogeny consisting of the proposed evolutionary relationships among the six haplotypes of P. infestans was also presented. The approach involved sequencing specific mtDNA regions that produced different haplotypes. In addition, a region encoding the nad 4L and nad 1 genes was used to distinguish P. infestans from a selected group of Phytophthora species were identified. Analysis of mtDNA variation and distribution provided fresh insights on the population genetics of P. infestans. Haplotype I-b was found only in the US-1 clonal lineage that migrated worldwide beginning in the 1800s. Haplotypes I-a and II-a were associated with diverse genotypes that migrated from Mexico into Europe, South America, and Asia in the 1970s. Haplotype II-b was found only in the US-6 clonal lineage that migrated from northwestern Mexico into the United States and Canada during the 1970s. The dominance of mtDNA haplotype I-a in the randomly mating population in the Toluca Valley of Mexico, the center of nuclear DNA (nDNA) diversity and presumed origin of P. infestans, is hypothesized to be driven by selection.--Abstract.